Gestão do conhecimento em equipas: Desenvolvimento de um instrumento de medida multidimensional - Cardoso, Leonor (2011)
This paper describes the development of the Team Knowledge Management (TKM). Following a deductive method, TKM was developed based on Cardoso’s (2003) model of knowledge management. This instrument allows the evaluation of fourteen dimensions of knowledge management distributed by six main sections: creation and acquisition of knowledge, attribution of meaning to the knowledge, knowledge share and diffusion, memory of the team, knowledge recovery and use, and knowledge management catalysts. Considering preliminary tests, the psychometric properties of TKM are satisfactory.